Edukasi Kegel Exercise terhadap Penyembuhan Luka Perineum - Yunitasari, Eva; Muddrikah, An-Nisaa; Fitri, Feni Elda (Universitas Pahlawan Tuanku Tambusai, 2026)
Kegel exercises are an effective non-pharmacological method of healing perineal wounds, helping to accelerate the healing of perineal wounds after childbirth caused by tears in the vagina and perineum. Slow healing of perineal wounds can lead to complications such as bleeding and even death in postpartum women. This community service activity aims to increase postpartum mothers' knowledge about Kegel exercises. The implementation method involves interactive counseling, direct demonstrations of how to perform Kegel exercises, and videos. The results of the activity showed an increase in knowledge, a change in attitude, and an improvement in the condition of the wounds of postpartum mothers after being given education on Kegel exercises. It is hoped that the community health center can continue to provide clear and regular information and education about the effects of Kegel exercises on the healing of perineal wounds for other postpartum mothers.